Case Study on Postpartum Mothers with Severe Preeclampsia Through 4 Hour Blood Pressure Monitoring - Apriliani, Annisa; Koeryaman, Mira Trisyani; Mamuroh, Lilis (Utami Publisher, 2026)
Preeclampsia is a pregnancy complication that can continue into the postpartum period and has the potential to cause serious organ disorders and increase the risk of maternal death. This condition can cause various complications, including seizures, impaired liver function and blood clotting, cerebral hemorrhage, fluid buildup in the lungs, and heart disease. One important effort in preventing these complications is regular blood pressure monitoring to ensure the effectiveness of antihypertensive therapy and hemodynamic stability. This case study aims to analyze the application of blood pressure monitoring every 4 hours in postpartum mothers with severe preeclampsia as an effort to detect complications early. This case study uses a descriptive approach with a single case study method on Mrs. N, 21 years old, postpartum day 1 with a history of Partus Maturus with Oxytocin Drip Augmentation: Severe Preeclampsia. For four days of care, the client received antihypertensive therapy 3 x 1 per day accompanied by blood pressure monitoring, physical examination and laboratory evaluation. Monitoring results showed that blood pressure continued to fluctuate until the fourth postpartum day, ranging from 127/90 mmHg to 180/120 mmHg, despite a decrease in edema from grade 3 to grade 2 and an improvement in hemoglobin levels. These findings indicate that despite clinical and laboratory improvements, the mother's hemodynamic condition was not stable until the fourth postpartum day. Therefore, intensive blood pressure monitoring and therapy evaluation are needed until blood pressure stability and optimal clinical improvement are achieved.